Entwicklung neuer Materialien für die additive Fertigung und das Rapid Prototyping von Glas und Polymethylmethacrylat - Kotz, Frederik (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie / Hrsg.: Institut für Mikrostrukturtechnik, 2018)
Curable nanocomposites were developed to fabricate fused silica glass. During a thermal debinding and sintering step a transparent fused silica glass is received. These nanocomposites can be structured using stereolithography or replicative processes. PMMA prepolymers were developed which can be structured using lithography in a few seconds. PFPEs were established as a stereolithography material.